2018
DOI: 10.3892/ijo.2018.4452
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant, aged garlic extract, exerts cytotoxic effects on wild-type and multidrug-resistant human cancer cells by altering mitochondrial permeability

Abstract: Aged garlic extract (AGE) has been shown to possess therapeutic properties in cancer; however its mechanisms of action are unclear. In this study, we demonstrate by MTT assay that AGE exerts an anti-proliferative effect on a panel of both sensitive and multidrug-resistant (MDR) human cancer cell lines and enhances the effects of hyperthermia (42˚C) on M14 melanoma cells. The evaluation of the mitochondrial activity in whole cancer cells treated with AGE, performed by cytofluorimetric analysis in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 68 publications
4
14
0
Order By: Relevance
“…Basic experiments have indicated that both aged garlic extract and fresh garlic extract had anticancer effects. The aged garlic extract had cytotoxic effects on cancer cells by activating K+/H+ exchange, causing oxidative stress in the mitochondria and inducing mitochondrial permeability transition (Ohkubo et al, ). Fresh garlic extract was suggested to suppress cancer cell proliferation, which was related to increased endoplasmic reticulum stress (Petrovic et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic experiments have indicated that both aged garlic extract and fresh garlic extract had anticancer effects. The aged garlic extract had cytotoxic effects on cancer cells by activating K+/H+ exchange, causing oxidative stress in the mitochondria and inducing mitochondrial permeability transition (Ohkubo et al, ). Fresh garlic extract was suggested to suppress cancer cell proliferation, which was related to increased endoplasmic reticulum stress (Petrovic et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, basic studies showed that aged garlic extract could suppress collagen-induced platelet aggregation via the inhibition of the P2X1 receptor, thromboxane receptor, and MAP kinase phosphorylation by acting on newly formed platelets from bone marrow megakaryocytes (Morihara & Hino, 2017), and it was also suggested that the aged garlic extract might inhibit platelet aggregation by increasing cyclic nucleotides and inhibiting fibrinogen binding and platelet shape change (Rahman, Lowe, & Smith, 2016). Although it was suggested that the aged garlic extract might influence the function of platelets, the results from animal studies indicated that the aged garlic extract was not associated with serious hemorrhagic risk (Morihara & Hino, 2017), and a randomized placebo-controlled study also showed that the daily consumption of 4.2 g raw garlic did not impair the platelet function of healthy participants (Scharbert, Kalb, Duris, Marschalek, & Kozek-Langenecker, 2007 (Ohkubo et al, 2018). Fresh garlic extract was suggested to suppress cancer cell proliferation, which was related to increased endoplasmic reticulum stress (Petrovic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…human cancer cells (1). Following treatment of the cells with AGE, cytofluorimetric analysis revealed the occurrence of dose-dependent mitochondrial membrane depolarization (MMD) (1).…”
Section: Aged Garlic Extract and Its Constituent S-allyl-l-cysteinementioning
confidence: 99%
“…human cancer cells (1). Following treatment of the cells with AGE, cytofluorimetric analysis revealed the occurrence of dose-dependent mitochondrial membrane depolarization (MMD) (1). A large number of epidemiological investigations have suggested that garlic is active in the prevention and treatment of various diseases with multiple pharmacological functions, such as anticarcinogenic (2), antithrombotic (3), hypolipidemic (4) and hepatoprotective (5) activities.…”
Section: Aged Garlic Extract and Its Constituent S-allyl-l-cysteinementioning
confidence: 99%
See 1 more Smart Citation